Respuesta :

Answer:

d = mn/F

Step-by-step explanation:

F = mn/d

multiply both sides with d

d*F = mn/d*d

dF=mn

divide F from both sides

d/F = mn/F

So..

d = mn/F

Answer:

Given:

[tex] \boxed{ \mathsf{F = \frac{mn}{d} }}[/tex]

Divide both sides by "mn":

[tex] \mathsf{ \frac{F}{mn} = \frac{mn}{d \times mn} }[/tex]

The two mn's on the RHS gets canceled out. So we're left with:

[tex] \mathsf{ \frac{F}{mn} = \frac{1}{d} }[/tex]

Invert the fractions present on either side of the "equals" sign

(In other words, flip it on its head so its numerator becomes its denominator and vice):

[tex] \mathsf{ \frac{mn}{F} = \frac{d}{1} }[/tex]

Hence, we got the value of d:

[tex] \underline{\mathsf{ d= \frac{mn}{F} }}[/tex]

ACCESS MORE